Factors related to controlled blood sugar levels in diabetes mellitus patients at Hospital - Tien Gartinah; Ita Yuanita; Yuli Amran (International Journal of Nursing and Midwifery Research, 2022)
Chronic disease is a disease condition or health problem related to symptoms or disabilities who need long-term management. The results showed that there were 75 people from 54 (72.0%) patients with diabetes who controlled their blood sugar levels, while 21 (28.0%) patients with diabetes who were not their blood sugar levels under control. Thus, the proportion of patients with uncontrolled blood sugar levels is more than in patients who do not have blood sugar levels under control. In addition, based on data analysis using chi square analysis, correlation and logistic regression obtained results indicate that there is no relationship between knowledge, education, proximity and exposure to sources of information, food intake, physical activity of the patient, the patient's drug intake, as well as other complications of disease (P value = 0.622; 0.612; 0.743; 0.903; 0.564; 0.503; 0.649) with control of blood sugar levels. Based on these research results suggest the author's family to better provide support to members who have diabetes in the family to perform control of blood sugar levels. For health workers in order to further enhance socialization, counseling and services in the management of diabetes mellitus to patients' blood sugar levels can be controlled, so as to improve health status.